Determinant of Corporate Social Responsibility Disclosure - Nuraini Fifianti; Prasetyono Prasetyono (JAFFA, 2019)
This research aims to analyze the effect of company characteristics on CSR (Corporate Social Responsibility) disclosure. This research was conducted at manufacturing companies listed on Indonesian Stock Exchange in 2014-2016. This research used purposive sampling method. The samples consisted 58 companies with a total of 174 observations. The characteristics of the company in this research were proxied by the company size, liquidity, and profitability. Data analysis technique used in the research was multiple linier regression analysis technique. Based on the result of the analysis, it can be concluded the company size variable affect CSR disclosure, while the liquidity, leverage, and profitability variables do not affect CSR disclosure